Material media-making in the digital age - Binns, Daniel (Intellect Books, 2021)
A journey through a variety of tools and technologies from vlogging to drone cinematography to considerations of time, editing, and sound design, Material Media-Making in the Digital Age offers professionals, scholars, and students alike the chance to re-think how they engage with new media technology, about media and its place in the world. 17 b/w illus.